The effects of different concentrations of Alum solutions on Mutans streptococci (in vitro study) - Raed F AI-Huwaizi; Wael S Al-Alousi (College of Dentistry/ University of Baghdad, 2014)
Background: Alum has been used as a treatment medication in cases of oral and gingival ulcers, and also as antiseptic mouthwash. This study aimed to examine the effects of different concentrations of Alum on inhibition zone, viability counts and adherence ability of Mutans streptococci compared with deionized water and chlorhexidine gluconate in vitro. Materials and methods: The study dealt with an in vitro study to establish a concentration of Alum mouthrinse that would have the minimum inhibitory concentration and minimum bacteriocidal concentration. The second part evaluated the anti-adherence ability of the experimental agents. Results: This study found that the antibacterial effect of Alum increases with its concentration from 50 to 10000 PPM but still weaker than 0.1% chlorhexidine gluconate. Only concentrations of 5000 and 10000 PPM showed negative adherence of Mutans streptococci to the tooth surface. Conclusions: This study found that the antibacterial effect of Alum increases with its concentration from 50 to 10000 PPM but still weaker than 0.1% chlorhexidine gluconate. Only concentrations of 5000 and 10000 PPM showed negative adherence of Mutans streptococci to the tooth surface.